2001
DOI: 10.1067/mhn.2001.115086
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Damage in Nasal Polyp Tissue

Abstract: High level of MDA in nasal polyp tissue that represents FR increase supports the existence of cell injury in nasal polyp tissue. FRs should be considered in the development and life cycles of NP which is thought to have multifactorial pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…Dogru et al 15 reported that malondialdehyde levels were higher in nasal polyposis than in control mucosa and Dagli et al 3 showed higher malondialdehyde levels in nasal polyp tissue and blood of patients with nasal polyposis compared with control individuals. Malondialdehyde results from the action of free radical damage to cellular lipids and leads to increased levels of free radicals; both free radicals and malondialdehyde injure cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Dogru et al 15 reported that malondialdehyde levels were higher in nasal polyposis than in control mucosa and Dagli et al 3 showed higher malondialdehyde levels in nasal polyp tissue and blood of patients with nasal polyposis compared with control individuals. Malondialdehyde results from the action of free radical damage to cellular lipids and leads to increased levels of free radicals; both free radicals and malondialdehyde injure cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…MPO is an enzyme, which occurs as a result of neutrophil activation, may lead to the formation of FOR such as H 2 O 2 , NO and especially, HOCL with other enzymes [13,14]. Several studies were performed to investigate the relationship of MPO with chronic sinusitis, role of FOR in the development of nasal polyps and the effects of antioxidant agents on the development of nasal polyps [7,15,16]. In a study carried out by Demoly et al regarding neutrophil infiltration in patients diagnosed with chronic investigators demonstrated the production of FOR in the neutrophils of nasal polyps and determined a very high ratio of FOR production in nasal polyps [16].…”
Section: Discussionmentioning
confidence: 99%
“…FOR are necessary for normal immune defense and metabolic activity in humans but also they may cause tissue damage if they are excessively produced and they may play an important role in the pathogenesis of various diseases [6,7]. Currently, there are several studies related with nasal polyps and their relationship with FOR [8,9] but up to date and as much as we are informed, there are a limited number of direct studies related with the role of myeloperoxydase(MPO) which is responsible in the formation of FOR, in the pathogenesis of polyps [10].…”
Section: Introductionmentioning
confidence: 99%
“…GSTM1 and GSTT1 genotyping GSTM1 and GSTT1 allele genotyping was carried out by using a multiplex PCR protocol (18). Briefly, the amplification was made in a total volume of 25 µl reaction mixture containing 12.5 µl 2xPCR Master Mix (Thermo Fischer Scientific Inc., MA, USA), 10 pmoles of each forward and reverse specific primers and free nucleases water to 25 µl.…”
Section: Methodsmentioning
confidence: 99%